DESENVOLVIMENTO DE UMA FERRAMENTA ASSISTENTE PARA CRIAÇÃO DE APLICAÇÕES CRUD EM JAVA NA WEB - Carlos Renato de Souza Perri; Francisco Assis da Silva; Leandro Luiz de Almeida (Colloquium Exactarum, 2010)
Due to the need for computerization of business processes, storage of relevant information in databases and making these information available on Internet, this project proposes to develop a tool for generating Web applications written in Java, that build functionalities to perform CRUD (Create, Retrieve, Update, Delete), ie, storage, read, update and deletion. The software is a tool, from which, the programmer inserts the script to create a database and, after setting the parameters into the tool, source code of Java Web applications are generated. There is a need to create Web applications in Java with low production time, because building these applications using common methods for development takes much time. The implementation of this tool is also to change that concept and the way of developing Java Web applications, because this tool will be used as an assistant, becoming easier to create Java Web applications. The generated applications use the technologies Servlets and JSPs, the Hibernate framework and the jQuery JavaScript library.